Ceramic copper circuit board and semiconductor device using the same

The ceramic copper circuit board addresses the issue of deteriorated TCT characteristics by using a brazing material layer without Ag, incorporating titanium-rich protrusions to enhance thermal and mechanical performance.

JP2025061058AActive Publication Date: 2025-04-10NITERRA MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025002123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-10-25
Filing Date
2025-01-07
Publication Date
2025-04-10
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

Existing ceramic circuit boards with brazing material layers lacking Ag suffer from deteriorated TCT characteristics due to the inability to form protrusions in the brazing material layer.

Method used

A ceramic copper circuit board with a brazing material layer that does not contain Ag, featuring a joint portion and a first protrusion portion with a titanium content of 70% to 100% by mass, and a second protrusion portion with a titanium content less than 70% by mass, is used to improve TCT characteristics.

Benefits of technology

The proposed solution effectively enhances the TCT characteristics of the ceramic copper circuit board while suppressing migration and improving stress relaxation effects, leading to improved performance in heat dissipation and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061058000001_ABST
    Figure 2025061058000001_ABST
Patent Text Reader

Abstract

To provide a ceramic copper circuit board using a Ag-free brazing filler metal layer, wherein the brazing filler metal layer of the ceramic copper circuit board includes a protruding part, and a semiconductor device using the same.SOLUTION: A ceramic copper circuit board according to the embodiment includes a ceramic substrate, and a plurality of copper circuit parts bonded respectively via brazing filler metal layers on at least one surface of the ceramic substrate. The brazing filler metal layer does not contain Ag and contains Cu, Ti, and one or two kinds selected from Sn and In. The brazing filler metal layer includes a junction provided between the ceramic substrate and the copper circuit part, and a first protruding part provided around the junction and having a titanium content in the range of 70 mass% or more and 100 mass% or less. When the thickness of the copper circuit part is D and the shortest distance between adjacent copper circuit parts is P, the thickness D of the copper circuit part is 0.1 mm or more, and a region satisfying 1≤P / D≤3 is included.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiments described below relate to a ceramic copper circuit board and a semiconductor device using the same. [Background technology]

[0002] In recent years, power modules are being used in electric vehicles and trains to control large currents and voltages due to the increasing performance of industrial equipment and global environmental issues. The heat generated by the semiconductor elements mounted on these devices is also increasing. For this reason, heat dissipation is becoming important for circuit boards for power modules. Ceramic-metal bonded circuit boards, in which a metal plate such as copper or aluminum is bonded to a highly thermally conductive ceramic substrate, are widely used. In addition, the active metal bonding method using brazing material is widely used as a method for bonding a ceramic substrate and a copper plate. The brazing material used in the active metal bonding method is called an active metal brazing material. For example, Japanese Patent No. 6158144 (Patent Document 1) discloses a ceramic circuit board using a brazing material layer containing Ag, Cu, and Ti. In Patent Document 1, a protruding portion of the brazing material layer is formed on the ceramic circuit board. According to Patent Document 1, the TCT characteristics are improved by forming the protruding portion of the brazing material layer. A bonding method using a brazing material layer containing Ag, Cu, and Ti as in Patent Document 1 is called an active metal bonding method. Generally, in the active metal bonding method, an active metal is contained in the brazing material, and Ag, Cu, and Ti are often used as the bonding brazing material. Among the bonding brazing materials, Ag is an expensive element. For example, Japanese Patent Application Laid-Open No. 2003-283064 (Patent Document 2) discloses the use of a CuSnTi-based brazing material that does not contain Ag. The ceramic circuit board of Patent Document 2 does not use Ag in the brazing material. Therefore, the brazing material layer has good etching properties. Patent Document 2 discloses an active metal brazing material that does not contain Ag. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6158144 [Patent Document 2] JP 2003-283064 A Summary of the Invention [Problem to be solved by the invention]

[0004] In Patent Document 2, the etching property of the brazing material layer is improved. On the other hand, it is not possible to form an overhanging portion of the brazing material layer as in Patent Document 1. Since an overhanging portion of the brazing material layer is not formed, there is a problem that the TCT characteristics of the ceramic circuit board is deteriorated. The ceramic copper circuit board according to the embodiment is characterized in that the protruding portion of the brazing material layer is controlled in the ceramic copper circuit board using the brazing material layer that does not contain Ag. [Means for solving the problem]

[0005] The ceramic copper circuit board according to the embodiment includes a ceramic substrate and a plurality of copper circuit parts each bonded to at least one surface of the ceramic substrate via a brazing material layer. The brazing material layer does not contain Ag, but contains Cu, Ti, and one or two selected from Sn and In. The brazing material layer includes a joint provided between the ceramic substrate and the copper circuit part, and a first protruding part provided around the joint and having a titanium content in the range of 70 mass % to 100 mass %. When the thickness of the copper circuit part is D and the shortest distance between the adjacent copper circuit parts is P, the thickness D of the copper circuit part is 0.1 mm or more and includes a portion where 1≦P / D≦3. [Brief description of the drawings]

[0006] [Figure 1] FIG. 2 is a schematic diagram showing an example of a ceramic copper circuit board according to an embodiment. [Diagram 2] FIG. 4 is a schematic diagram showing another example of a ceramic copper circuit board according to an embodiment. [Diagram 3] FIG. 2 is a schematic diagram showing an example of a protruding portion of a ceramic copper circuit board according to an embodiment. [Figure 4] 4 is a schematic diagram showing the length of a first protruding portion and the length of the entire protruding portion. FIG. [Diagram 5] FIG. 13 is a conceptual diagram illustrating a method for measuring the inclination angle of a side surface of a copper circuit portion. [Figure 6] 1 is a schematic diagram showing an example of a semiconductor device according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The ceramic copper circuit board according to the embodiment includes a ceramic substrate and a plurality of copper circuit parts each bonded to at least one surface of the ceramic substrate via a brazing material layer. The brazing material layer does not contain Ag, but contains Cu, Ti, and one or two selected from Sn and In. The brazing material layer includes a joint provided between the ceramic substrate and the copper circuit part, and a first protruding part provided around the joint and having a titanium content in the range of 70 mass % to 100 mass %. When the thickness of the copper circuit part is D and the shortest distance between the adjacent copper circuit parts is P, the thickness D of the copper circuit part is 0.1 mm or more and includes a portion where 1≦P / D≦3. Fig. 1 is a schematic diagram showing an example of a ceramic copper circuit board according to an embodiment. Fig. 2 is a schematic diagram showing another example of a ceramic copper circuit board according to an embodiment. Fig. 3 is a schematic diagram showing an example of a protruding portion of a ceramic copper circuit board according to an embodiment. In Figs. 1 to 3, reference numeral 1 denotes a ceramic copper circuit board, reference numeral 2 denotes a ceramic substrate, reference numeral 3 denotes a copper circuit portion, reference numeral 4 denotes a brazing layer, reference numeral 5 denotes a joint portion, reference numeral 6 denotes a first protruding portion, reference numeral 7 denotes a second protruding portion, and reference numeral 8 denotes a copper heat sink. L1 denotes the length of the first protruding portion 6, and L2 denotes the length of the entire protruding portion. The ceramic copper circuit board 1 according to the embodiment has a structure in which a copper circuit portion 3 is bonded to at least one surface of a ceramic substrate 2 via a brazing material layer 4. As shown in Fig. 1, the copper circuit portion 3 may be bonded to one surface of the ceramic substrate 2, and a copper heat sink plate 8 may be bonded to the other surface of the ceramic substrate 2. As shown in Fig. 2, a plurality of copper circuit portions 3 may be bonded to one surface of the ceramic substrate 2. The copper circuit portion 3 may be provided instead of the copper heat sink plate 8.

[0008] Examples of the ceramic substrate 2 include a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, and a zirconium oxide substrate. The ceramic substrate 2 is preferably either a silicon nitride substrate or an aluminum nitride substrate. The silicon nitride substrate and the aluminum nitride substrate are nitride-based ceramic substrates. As described later, a titanium nitride layer can be formed on the nitride-based ceramic substrate by an active metal bonding method. The aluminum oxide substrate and the zirconium oxide substrate are oxide-based ceramic substrates. A titanium oxide layer can be formed on the oxide-based ceramic substrate by an active metal bonding method. When comparing the nitride-based ceramic substrate with the oxide-based ceramic substrate, the nitride-based ceramic substrate has a higher thermal conductivity. From this point of view, it is preferable to use the nitride-based ceramic substrate. The thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 3 mm or less. If the substrate thickness is less than 0.1 mm, the strength may decrease. If the substrate thickness is thicker than 3 mm, the ceramic substrate may become a thermal resistor, which may decrease the heat dissipation of the bonded body. For this reason, the thickness of the ceramic substrate 2 is preferably 0.1 mm or more and 3 mm or less, and more preferably 0.2 mm or more and 1 mm or less.

[0009] The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity of the silicon nitride substrate is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the substrate thickness can be reduced. For this reason, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, and more preferably 700 MPa or more. The substrate thickness of the silicon nitride substrate can be reduced to 0.40 mm or less, and even to 0.30 mm or less. The three-point bending strength of an aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of an aluminum nitride substrate is 160 W / m·K or more. Since the strength of an aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more. Copper plates or copper alloy plates can be used for the copper circuit section 3 and the copper heat sink 8. The copper circuit section 3 and the copper heat sink 8 are preferably made of oxygen-free copper. As specified in JIS-H-3100 (ISO1337, etc.), oxygen-free copper is copper with a copper purity of 99.96 wt% or more. By making the copper circuit section 3 and the copper heat sink 8 thicker, the current carrying capacity and heat dissipation can be improved. For this reason, the thickness of the copper circuit section 3 and the copper heat sink 8 is preferably 0.1 mm or more, more preferably 0.6 mm or more. More preferably, the thickness of the copper circuit section 3 and the copper heat sink 8 is 0.8 mm or more.

[0010] The copper circuit portion 3 and the copper heat sink 8 are each joined to the ceramic substrate 2 via a brazing material layer 4. The brazing material layer 4 includes a joint portion 5. The joint portion 5 is provided between the ceramic substrate 2 and the copper circuit portion 3 or between the ceramic substrate 2 and the copper heat sink 8. The brazing material layer 4 further includes a protruding portion provided around the joint portion 5 in the in-plane direction. The in-plane direction is a direction parallel to the surface of the ceramic substrate 2. The brazing material layer 4 is provided on that surface of the ceramic substrate 2. The protruding portion protrudes from the end of the copper circuit portion 3 or the copper heat sink 8 along the in-plane direction. 1, the protruding portion includes a first protruding portion 6. In the first protruding portion 6, the titanium content is in the range of 70 mass % or more and 100 mass % or less. In the first protruding portion 6, the total titanium content and nitrogen content is preferably in the range of 90 mass % or more and 100 mass % or less. As shown in FIG. 2, the protruding portion may further include a second protruding portion 7. The second protruding portion 7 is provided between the joint portion 5 and the first protruding portion 6. The second protruding portion 7 has a titanium content of less than 70 mass %. The brazing material layer 4 has a structure in which the joint portion 5, the second protruding portion 7, and the first protruding portion 6 are connected to each other. The first protruding portion 6 is located outside the protruding portion. The second protruding portion 7 is located inside the protruding portion. As shown in Fig. 3, the boundary between the joint 5 and the protruding portion is based on the end of the copper circuit portion 3 or the copper heat sink 8. A line perpendicular to the surface of the ceramic substrate 2 is drawn from the end of the copper circuit portion 3 or the copper heat sink 8. The portion protruding from the perpendicular line is the protruding portion. The protruding portion of the brazing material layer is also simply called the protruding portion.

[0011] A scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) is used to measure the titanium content in the protruding portion. An area analysis is performed on the protruding portion in any cross section of the ceramic copper circuit board 1. In the area analysis, the measurement area is set so that the entire protruding portion is the subject of analysis. The entire protruding portion refers to the portion of the brazing material layer 4 other than the joint portion 5, and the entire portion protruding from the boundary between the ceramic substrate 2 and the protruding portion. When a copper plate is joined to a silicon nitride substrate using a Ti-containing brazing material layer, a titanium nitride layer is formed on the surface of the silicon nitride substrate. The boundary between the silicon nitride substrate and the titanium nitride layer is the boundary between the ceramic substrate 2 and the brazing material layer 4. In other words, the titanium nitride layer is part of the joint 5 and part of the protruding portion. For this reason, when analyzing the area, care must be taken to include the titanium nitride layer in the measurement area and not include the silicon nitride substrate. When a copper plate is joined to an oxide-based ceramic substrate using a Ti-containing brazing filler layer, a titanium oxide layer is formed on the surface of the oxide-based ceramic substrate. The boundary between the oxide-based ceramic substrate and the titanium oxide layer is the boundary between the ceramic substrate 2 and the brazing filler layer 4. When analyzing the area, care should be taken to ensure that the titanium oxide layer is included in the measurement area, but that the oxide-based ceramic substrate is not included in the measurement area. For SEM observation, a Field Emission SEM (FE-SEM) is used. EDX is sometimes called EDS. For FE-SEM, a JEOL JSM-7200F or a device with equivalent performance is used. For EDX, a JEOL EX-74600U4L2Q or a device with equivalent performance is used. The measurement conditions for FE-SEM were: acceleration voltage 15 kV, magnification 3000x, field of view area 1200 μm 2 (=30 μm in thickness direction × 40 μm in width direction). The thickness direction is perpendicular to the surface of the ceramic substrate 2. The width direction is parallel to the cross-sectional and in-plane directions. The EDX measurement conditions are set to 50 scans and a measurement speed of 0.2 ms / bit. When performing EDX area analysis, the capture pixels are 256 × 198 pixels, the detection count is 3700 to 4100 cps (counts per second), and the quantitative map is 5 × 5 bit / point. Area analysis is sometimes called surface analysis. Regarding EDX, it is effective to first investigate the elements that make up the brazing material layer using qualitative analysis with EDX, and then identify the elements to be identified before performing area analysis. When measuring the amount of titanium in the protruding portion of a ceramic copper circuit board 1 using a nitride ceramic substrate, the total of the metal components, silicon, nitrogen, and carbon is taken as 100% by mass. When measuring the amount of titanium in the protruding portion of a ceramic copper circuit board using an oxide ceramic substrate, the total of the metal components, oxygen, and carbon is taken as 100% by mass. Metal components are measured in amounts of 0.01% by mass or more. This is because amounts less than 0.01% by mass are below the detection limit of EDX. When a silicon nitride substrate is used as a nitride ceramic substrate, silicon and nitrogen diffuse into the brazing material layer. As a result, silicon and nitrogen are included in the measurement targets. Similarly, for aluminum nitride substrates, Al and nitrogen are included in the measurement targets. For aluminum oxide substrates, Al and oxygen are included in the measurement targets. For zirconium oxide substrates, Zr and oxygen are included in the measurement targets. Al and Zr are included in the measurement targets as types of metal components.

[0012] The first protruding portion 6 is a region in which the titanium content is 70% by mass or more and 100% by mass or less. When a nitride ceramic substrate is used, the tip of the protruding portion may be composed of only titanium or titanium nitride. The first protruding portion 6 is preferably a region in which the total titanium content and nitrogen content is 90% by mass or more and 100% by mass or less. The amount of titanium nitride in the first protruding portion 6 is counted assuming that all nitrogen detected by EDX constitutes titanium nitride (TiN). When an oxide ceramic substrate is used, the tip of the protruding portion may be composed of only titanium or titanium oxide. The first protruding portion 6 is preferably an area in which the total titanium content and oxygen content is 90% by mass or more and 100% by mass or less. Regarding the amount of titanium oxide in the first protruding portion 6, all of the oxygen detected by EDX is titanium oxide (TiO 2 ) and count the amount of titanium oxide. An example in which a nitride ceramic substrate is used will be described below. When an oxide ceramic substrate is used, the titanium nitride in the protruding portion can be replaced with titanium oxide. As described later, the brazing material layer 4 contains Cu (copper), Ti (titanium), and one or two selected from Sn (tin) and In (indium). Components other than titanium and nitrogen in the first protruding portion 6 include Cu, Sn, and In. If a large amount of these components remain, migration is likely to occur between the copper circuit portions when the distance between adjacent copper circuit portions 3 is shortened. Migration is a phenomenon in which, when a circuit board is placed in a humid environment, ionized metal moves between electrodes due to the application of voltage, causing a short circuit. Migration caused by ionized metal is called ion migration. In recent years, semiconductor devices have been used in various industrial equipment. For example, electric vehicles are sometimes used in humid environments. In the active metal bonding method, Ag, Cu, Sn, In, Ti, and the like are used as bonding brazing materials. Among these, Ti has a low ionization tendency and is resistant to moisture. Ti reacts with a nitride-based ceramic substrate to become titanium nitride. The formation of titanium nitride can suppress the occurrence of migration. For this reason, the titanium content in the first protruding portion 6 must be within a range of 70% by mass or more and 100% by mass or less. Furthermore, it is preferable that the total of the titanium content and the nitrogen content in the first protruding portion 6 is 90% by mass or more and 100% by mass or less, and further 99% by mass or more and 100% by mass or less.

[0013] The titanium content in the second protruding portion 7 is less than 70 mass %. That is, the second protruding portion 7 contains components other than titanium in an amount of 30 mass % or more. As described above, migration is suppressed by increasing the amount of titanium (or titanium nitride) contained in the first protruding portion 6. On the other hand, if the amount of titanium (or titanium nitride) increases too much, the stress relaxation effect in the vicinity of the end of the copper circuit portion 3 or the copper heat sink 8 decreases. For this reason, it is effective for the titanium content of the second protruding portion 7 to be less than 70 mass %. In the second protruding portion 7, it is preferable that the Cu content is 5 to 60 mass%, the Sn or In content is 5 to 45 mass%, and the total content of Ti and titanium nitride is 10 to less than 90 mass%. The presence of predetermined amounts of Cu and one or two selected from Sn and In can improve the stress relaxation effect in the vicinity of the end portion of the copper circuit portion 3. The brazing material layer 4 contains Cu, Ti, and one or two selected from Sn and In. The content of Ag in the brazing material layer 4 is preferably 0% by mass or more and 10% by mass or less. The brazing material layer 4 may contain components other than Cu, Ti, Sn, and In. On the other hand, if the Ag content in the brazing material layer 4 is large, it may be difficult to form the first protruding portion 6. For this reason, the Ag content in the brazing material layer 4 is preferably 10% by mass or less. More preferably, the Ag content in the brazing material layer 4 is 0% by mass, and the brazing material layer 4 does not contain Ag. The Ag content of 0% by mass means that it is below the detection limit (less than 0.01% by mass) by EDX. The brazing material layer 4 may contain 10% by mass or less of metal elements other than Cu, Ti, Sn, and In. Examples of metal elements other than Cu, Ti, Sn, and In include one or more selected from carbon, magnesium, molybdenum, tungsten, and rhenium. The brazing material layer 4 may contain these elements so long as the total content of these elements is 10 mass % or less.

[0014] The Cu content (mass%) of the joint 5 is C1. The Cu content (mass%) of the second protruding portion 7 is C2. The mass ratio C2 / C1 is preferably 0.7 or less. This indicates that the amount of Cu decreases from the joint 5 to the second protruding portion 7 to the first protruding portion 6 near the end of the copper circuit portion 3. By providing a gradient in the composition of the Cu amount, the stress relaxation effect can be improved. If the mass ratio C2 / C1 exceeds 0.7, the difference between the Cu amount in the second protruding portion 7 and the Cu amount in the first protruding portion 6 becomes too large, and the stress relaxation effect may decrease. The lower limit of the mass ratio C2 / C1 is not particularly limited, but is preferably 0.1 or more. If the mass ratio C2 / C1 is less than 0.1, the amount of Cu in the second protruding portion 7 may be too small, which may reduce the stress relaxation effect. For this reason, the mass ratio C2 / C1 is preferably 0.1 or more and 0.7 or less, and more preferably 0.2 or more and 0.5 or less. The amount of Cu in the joint 5, the amount of Cu in the first protruding portion 6, and the amount of Cu in the second protruding portion 7 are measured using the above-mentioned SEM-EDX area analysis. First, the brazing material layer 4 is divided into a joint 5 and an extruding portion according to the position of the end of the copper circuit portion 3 or the copper heat sink 8. Next, the extruding portion is divided into a region of the first protruding portion 6 and a region of the second protruding portion 7 according to the amount of Ti. The average value of the Cu amount in the joint 5 is defined as the Cu amount in the joint 5. The average value of the Cu amount in the region of the first protruding portion 6 is defined as the Cu amount in the first protruding portion 6. The average value of the Cu amount in the region of the second protruding portion is defined as the Cu amount in the second protruding portion 7. Regarding the amount of Cu in each of the joint 5, the first protruding portion 6, and the second protruding portion 7, five measurement areas are analyzed by EDX, and the amount of Cu in each of the joint 5, the first protruding portion 6, and the second protruding portion 7 included in each measurement area is measured. For each of the joint 5, the first protruding portion 6, and the second protruding portion 7, the average value of the amount of Cu in the five measurement areas is calculated, and the obtained average value is regarded as the amount of Cu in each part. The five measurement areas are obtained from five mutually different cross sections. Multiple cross sections passing through multiple sides of the copper circuit portion 3 in the ceramic copper circuit board 1 may be obtained, or multiple cross sections may be obtained from one side.

[0015] The Ti content (mass%) of the joint 5 is C3. The Ti content (mass%) of the second protruding portion 7 is C4. The mass ratio C4 / C3 is preferably 1.2 or less. By setting the mass ratio C4 / C3 to 1.2 or less, a gradient in the Ti content composition can be imparted from the joint 5 toward the second protruding portion 7. When the mass ratio C4 / C3 exceeds 1.2, it indicates that the second protruding portion 7 contains less Cu or Sn. The lower limit of the mass ratio C4 / C3 is not particularly limited, but is preferably greater than 1. For this reason, the mass ratio C4 / C3 is preferably greater than 1 and less than 1.2. The above-mentioned SEM-EDX area analysis is used to measure the Ti content of each of the joint 5 and the second protruding portion 7. The average value of the Ti content in the region of the second protruding portion 7 is taken as the Ti content of the second protruding portion 7. The Ti content of the joint 5 is taken as the average value of the Ti content in a region 100 μm inward from the boundary between the joint 5 and the protruding portion. Regarding the Ti content of each of the joint 5 and the second protruding portion 7, five measurement areas are analyzed by EDX, and the Ti content of each of the joint 5 and the second protruding portion 7 included in each measurement area is measured. For each of the joint 5 and the second protruding portion 7, the average value of the Ti content in the five measurement areas is calculated, and the obtained average value is the Ti content of each part. The five measurement areas are obtained from five mutually different cross sections. Multiple cross sections passing through multiple sides of the copper circuit part of the ceramic copper circuit board may be obtained, or multiple cross sections may be obtained from one side. The five cross sections for measuring the Cu content may be used to measure the Ti content together with the Cu content.

[0016] 3, the length of the first protruding portion 6 in the direction from the joint 5 toward the first protruding portion 6 is defined as L1. The length of the entire protruding portion in that direction is defined as L2. In this case, it is preferable to satisfy 0.3≦L1 / L2≦1. More preferably, it is 0.5≦L1 / L2≦0.8. As described above, the presence of the first protruding portion 6 and the second protruding portion 7 suppresses migration and provides stress relaxation effects. The length L2-length L1 corresponds to the length of the second protruding portion 7. These characteristics can be further improved by controlling the length of the first protruding portion 6 and the length of the second protruding portion 7. In particular, Ag migration can be suppressed by not including Ag in the joint portion 5 and the protruding portion of the brazing material layer. An active metal brazing material is used to join the ceramic substrate 2 and the copper circuit portion 3. In general, active metal brazing materials contain metals such as Ag, Cu, Ti, Sn, and In, but Ag is the element that is most likely to cause migration among active metal brazing materials. By reducing the Ag content or not including Ag, Ag migration can be suppressed. The length (L1) of the first protruding portion 6 and the length (L2-L1) of the second protruding portion 7 are measured by the above-mentioned area analysis of SEM-EDX. Specifically, from the results of the area analysis, a region on the upper surface of the protruding portion where the titanium content is 70 mass% or more is identified. From the identified region, the region that is connected to the tip of the protruding portion is extracted. The tip of the protruding portion is the point that is the furthest from the joint portion 5 among the points where the ceramic substrate 2 and the first protruding portion 6 are in contact. From the extracted region, the point closest to the copper circuit portion 3 is identified. A line perpendicular to the surface of the ceramic substrate 2 is drawn from the point closest to the copper plate. The length from the tip of the protruding portion to the perpendicular line is defined as the length L1 of the first protruding portion 6. The length (L2-L1) obtained by subtracting the length L1 of the first protruding portion 6 from the length L2 of the entire protruding portion is defined as the length of the second protruding portion 7. For example, if the region where the titanium content is 70 mass % or more is discontinued on the upper surface of the protruding portion, the length L1 of the first protruding portion is obtained using the region connected to the tip of the protruding portion. Figures 4(a) to 4(c) are schematic diagrams showing the length of the first protruding portion and the length of the entire protruding portion. In Figures 4(a) to 4(c), reference numeral 6 denotes the first protruding portion, and reference numeral 7 denotes the second protruding portion. In the example shown in Fig. 4(a), a first protruding portion 6 is present at the tip of the protruding portion. A region in which the titanium content is 70 mass% or more forms a single mass. In such a case, the location of the first protruding portion 6 on the upper surface of the protruding portion that is closest to the copper circuit portion 3 is identified, and the length L1 is measured. 4(b), the second protruding portion 7 is present on the upper surface of the protruding portion between a part of the first protruding portion 6 and another part of the first protruding portion 6. In this case, the length from the boundary between the part of the first protruding portion 6 connected to the tip of the protruding portion and the second protruding portion 7 on the upper surface of the protruding portion to the tip of the protruding portion is defined as length L1. 4(c), there are a plurality of first protruding portions 6 that are separated from each other on the upper surface of the protruding portion. A second protruding portion 7 is present between the first protruding portions 6. In this case, the length from the boundary between one first protruding portion 6 connected to the tip of the protruding portion and the second protruding portion 7 on the upper surface of the protruding portion to the tip of the protruding portion is defined as length L1.

[0017] The joint 5 may contain carbon. The joint 5 containing carbon means that the brazing filler metal contains carbon. By making the brazing filler metal contain carbon, the fluidity of the brazing filler metal can be controlled. This allows the brazing filler metal paste to be applied uniformly. When the joint 5 contains carbon, the first protruding portion 6 or the second protruding portion 7 may also contain carbon. The carbon content in the joint 5 is preferably within a range of 0.01% by mass to 2% by mass, more preferably 0.05% by mass to 1% by mass. The carbon content in the first protruding portion 6 or the second protruding portion 7 is also preferably within a range of 0% by mass to 1% by mass.

[0018] The inclination angle θ of the side surface of the copper circuit portion 3 is preferably within a range of 30° or more and 70° or less. Fig. 5 is a conceptual diagram illustrating a method for measuring the inclination angle of the side surface of the copper circuit portion. In Fig. 5, reference numeral 3 is the copper circuit portion, reference numeral 6 is a first protruding portion, and reference numeral 7 is a second protruding portion. Point A is the contact point between the end portion of the copper circuit portion 3 and the brazing material layer 4. Point B is the midpoint in the thickness direction of the side surface of the copper circuit portion 3. Point C is the intersection point of the horizontal line from point A and the vertical line from point B. The inclination angle θ is measured using an SEM photograph of an arbitrary cross section of the ceramic copper circuit board 1. An SEM photograph taken when the protruding portion is analyzed by SEM-EDX may also be used. First, on the cross-sectional photograph, point A is set as the contact point between the end of the copper circuit part 3 and the brazing material layer 4, and point B is set as the midpoint in the thickness direction of the side of the copper circuit part 3. Next, point C is set as the intersection point of a horizontal line from point A and a vertical line from point B. A right triangle is created between the three points ABC. The angle between sides BC and AB is set as the inclination angle θ of the side of the copper circuit part 3. The inclination angle θ of the side of the copper circuit part 3 is sometimes simply called the inclination angle θ. By setting the inclination angle θ within the range of 30° or more and 70° or less, the stress at the joint end portion can be alleviated. If the inclination angle is less than 30°, the inclined surface of the copper circuit portion 3 becomes longer, and the area for mounting the semiconductor element may become smaller. If the inclination angle θ exceeds 70°, the stress alleviation effect at the joint end portion may be insufficient. For this reason, the inclination angle θ is preferably within the range of 30° or more and 70° or less, and more preferably within the range of 40° or more and 60° or less.

[0019] A plurality of copper circuit portions 3 may be joined to at least one surface of the ceramic substrate 2. The shortest distance between adjacent copper circuit portions 3 may be within a range of 0.2 mm or more and 2 mm or less. Fig. 6 is a schematic diagram showing an example of a semiconductor device according to an embodiment. In Fig. 6, reference numeral 9 denotes a semiconductor element, and reference numeral 10 denotes a semiconductor device. The other reference numerals are the same as those in Fig. 1. P denotes the shortest distance between adjacent copper circuit portions 3. The shortest distance between adjacent copper circuit portions 3 is sometimes called the pitch. When an inclined surface is provided to the copper circuit portion 3, the shortest distance between the side end portions of the copper circuit portion 3 becomes the pitch P. In other words, the distance between the contact points of the end portions of the copper circuit portion 3 and the protruding portion of the brazing material layer becomes the pitch P. The pitch P being within the range of 0.2 mm or more and 2 mm or less indicates that the distance between adjacent copper circuit parts 3 is close. If the size of the ceramic substrate is the same, the bonding area of ​​the copper circuit part 3 can be increased by the close distance between adjacent copper circuit parts 3. That is, the mounting area of ​​the semiconductor element 9 or the like can be increased. Also, if the size of the copper circuit part 3 is the same, the size of the ceramic copper circuit board 1 can be reduced. That is, the ceramic copper circuit board 1 can be miniaturized without reducing the mounting area of ​​the semiconductor element 9 or the like. In the ceramic copper circuit board 1 according to the embodiment, the pitch P does not have to be within the range of 0.2 mm or more and 2 mm or less. On the other hand, when the pitch P is within the range of 0.2 mm or more and 2 mm or less, the above-mentioned effect can be obtained. Also, when three or more copper circuit parts 3 are bonded, it is preferable that there are two or more places where the pitch P is within the range of 0.2 mm or more and 2 mm or less. For example, the shortest distance between one copper circuit part 3 and another copper circuit part 3 adjacent to that one copper circuit part 3 is within the range of 0.2 mm or more and 2 mm or less. The shortest distance between the other copper circuit portion 3 and the further copper circuit portion 3 adjacent to the other copper circuit portion 3 is within the range of 0.2 mm or more and 2 mm or less. When the thickness of the copper plate is D, it is preferable to satisfy 1≦P / D≦3. Migration can occur not only at the tip of the protruding portion of the brazing material layer, but also on the side surface of the copper circuit portion 3. For this reason, it is preferable to set the pitch P according to the thickness D of the copper circuit portion 3.

[0020] The ceramic copper circuit board 1 as described above can be applied to a semiconductor device 10 on which a semiconductor element 9 is mounted. As shown in FIG. 6, the semiconductor element 9 is mounted on the copper circuit section 3. In the example shown in FIG. 6, one semiconductor element 9 is mounted. A plurality of semiconductor elements 9 may be mounted on each of a plurality of copper circuit sections 3. A lead frame or wire bonding may be provided as necessary. Furthermore, a plating film or molded resin may be provided on the surface of the copper circuit section 3 as necessary. The ceramic copper circuit board 1 according to the embodiment can suppress the occurrence of migration. Furthermore, by setting the pitch P within the range of 0.2 mm to 2 mm or satisfying 1≦P / D≦3, the occurrence of migration can be further suppressed.

[0021] Next, a method for manufacturing the ceramic copper circuit board 1 according to the embodiment will be described. The method for manufacturing the ceramic copper circuit board 1 according to the embodiment is not limited as long as it has the above-mentioned configuration. As an example, the following method can be used to obtain the ceramic copper circuit board 1 with a high yield. First, a ceramic substrate 2 is prepared. Examples of the ceramic substrate 2 include a silicon nitride substrate and an aluminum nitride substrate. A copper plate or a copper alloy plate can be used as a member for forming the copper circuit portion 3 or the copper heat sink 8. The copper plate is preferably oxygen-free copper. As specified in JIS-H-3100, oxygen-free copper is copper with a copper purity of 99.96 wt% or more. JIS-H-3100 (2018) corresponds to ISO1337 and the like. Next, a brazing filler metal is prepared. The brazing filler metal preferably contains 50% by mass or more of Cu, 4% by mass to 30% by mass of Ti, 5% by mass to 45% by mass of one or two selected from Sn and In, and 0% by mass to 2% by mass of carbon. Ti is titanium hydride (TiH 2 It is effective not to add Ag to the brazing filler metal. 2 A brazing filler metal containing Ti (including Ti) is an active metal brazing filler metal. As described later, when the heat bonding process is performed using a continuous furnace, the Ti content is preferably 2 mass% or more, and more preferably 5 mass% or more. In a continuous furnace, the heat bonding process is performed in a nitrogen atmosphere. By increasing the Ti content in the active metal brazing filler metal, it is possible to ensure that Ti contributes to bonding even if Ti reacts with the nitrogen atmosphere.

[0022] Average particle size D of Cu powder used as the raw material for brazing material 50The diameter of the Ti powder or TiH is preferably 12.0 μm or less, more preferably 10.0 μm or less. 2 Average powder particle size D 50 The average particle size D of the Sn powder or the In powder is preferably 6.0 μm or less, more preferably 4.0 μm or less. 50 The average particle diameter D of the carbon powder is preferably 16.0 μm or less, more preferably 14.0 μm or less. 50 The particle size is preferably 6.0 μm or less, more preferably 4.0 μm or less. By controlling the particle size of the powder, the reaction of each powder can be made uniform. Although a small amount of Ag may be added to the raw material, it is preferable not to add it. Average particle size of Cu powder D 50 is the average particle size D of the Sn or In powder 50 As described above, Cu and one or two selected from Sn and In form the base material of the brazing material composition. The melting point of Sn or In is lower than the melting point of Cu. By controlling the particle size of Sn or In, the reaction between the Sn or In powder and the Cu powder can be made uniform. When metal elements other than Cu, Ti, Sn, and In are added to the brazing material, the average particle size D of the powder of the metal element is 50 is the average particle size D of the Sn or In powder. 50 The metal elements other than Cu, Ti, Sn, and In include one or more selected from carbon, magnesium, molybdenum, tungsten, rhenium, and cobalt. These elements may be added to the raw material as long as the total amount of these elements is 10 mass% or less.

[0023] A process is carried out in which the ceramic substrate 2 and the copper plate are joined using the above-mentioned brazing material. The brazing material is mixed with an organic substance to prepare a brazing material paste. The brazing material paste is applied to the surface of the ceramic substrate 2 (or the copper plate) to form a brazing material paste layer. The copper plate (or the ceramic substrate 2) is placed on the brazing material paste layer. The laminate of the ceramic substrate, brazing material paste, and copper plate is called a pre-bonding laminate.

[0024] Either a batch type or a continuous type may be used for the heat bonding process. The batch type is a type in which the pre-bonding laminate is placed in a storage container and subjected to heat treatment. The continuous type is a type in which the pre-bonding laminate is placed on a belt conveyer and subjected to heat treatment while being moved. The batch type is suitable for a bonding process in a vacuum. The continuous type is suitable for a bonding process in a nitrogen atmosphere. A batch type heat bonding device is sometimes called a batch furnace. A continuous type heat bonding device is sometimes called a continuous furnace. In the batch process, the heating temperature is 750°C to 850°C, and the pressure is 10 -3 It is preferable that the vacuum is equal to or less than Pa. In the continuous type, the heating temperature is preferably within the range of 750° C. or more and 950° C. or less. In the continuous method, the heat bonding step is performed in a nitrogen atmosphere. The nitrogen atmosphere is an atmosphere containing 70 vol% or more of nitrogen. The nitrogen atmosphere preferably contains 70 vol% or more of nitrogen, and more preferably 85 vol% or more and 100 vol% or less. In addition to nitrogen gas, the nitrogen atmosphere may be an inert gas or air. When the heat bonding step is performed in a nitrogen atmosphere, the heat bonding step may be performed under various conditions such as normal pressure, reduced pressure, or increased pressure.

[0025] The thermal bonding process includes a temperature increase process, a holding process, and a temperature decrease process. In the temperature increase process, the temperature is increased from, for example, room temperature to the bonding temperature. The holding process is performed after the temperature increase process, and the bonding temperature is held. In the temperature decrease process, the temperature is decreased from the bonding temperature to, for example, room temperature. In the continuous heating process, the heating rate is set to 30° C. / min or more. The upper limit of the heating rate is not particularly limited, but 100° C. / min or less is preferable. If the heating rate is faster than 100° C. / min, the bonding property may be reduced. For this reason, the heating rate is preferably 30° C. / min or more and 100° C. / min or less, more preferably 40° C. / min or more and 70° C. / min or less. The bonding temperature is preferably 750°C or higher. The upper limit of the bonding temperature is preferably 1000°C or lower. If the bonding temperature is higher than 1000°C, the bonding temperature approaches the melting point of copper (1085°C) and there is a possibility that the copper plate will deform. For this reason, the bonding temperature is preferably 750°C or higher and 1000°C or lower, and more preferably 800°C or higher and 950°C or lower. In the holding step, the bonding temperature is held for 10 minutes or more. The time during which the bonding temperature is held is called the heating holding time. The heating holding time is preferably 10 minutes or more and 100 minutes or less. If the heating holding time is less than 10 minutes, there is a possibility that the time for the brazing material to melt or solidify is insufficient. If the heating holding time is longer than 100 minutes, there is a possibility that Sn or In will diffuse too much into the copper plate.

[0026] In the temperature decreasing step after the holding step, the temperature decreasing rate is set to 30° C. / min or more. The upper limit of the temperature decreasing rate is not particularly limited, but 100° C. / min or less is preferable. If the temperature decreasing rate is faster than 100° C. / min, the bondability may decrease. For this reason, the temperature decreasing rate is preferably 30° C. / min or more and 100° C. / min or less, more preferably 40° C. / min or more and 70° C. / min or less. The difference between the heating rate and the temperature drop rate is preferably 20° C. / min or less. In other words, it is preferable to satisfy |heating rate-temperature drop rate|≦20° C. / min. By heating the brazing paste, a melting reaction and a solidification reaction occur. These reactions occur in a heating process and a temperature drop process. By reducing the difference between the heating rate and the temperature drop rate, the stresses generated by the melting reaction and the solidification reaction can be homogenized. This makes it possible to suppress defects such as warping. If necessary, the heating and bonding process may be performed while a weight is placed on the bonded body.

[0027] The laminated body before bonding is subjected to the heat bonding process and is called a bonded body. The obtained bonded body is etched to impart a pattern shape to the copper plate. By imparting a pattern shape to the copper plate, a copper circuit part 3 is formed. A ceramic copper circuit board 1 equipped with a copper circuit part 3 is obtained. If necessary, a scribing process may be performed to obtain multiple pieces. Multi-piece production is a method in which a large bonded body is cut to obtain small bonded bodies. There are also methods of dividing the bonded body or dividing the ceramic copper circuit board. In the etching step, the copper plate is etched to form the copper circuit portion 3 and the copper heat sink plate 8. By etching the copper plate, a part of the brazing material layer 4 is exposed. Next, a step of etching the brazing material layer 4 is performed. It is preferable that the step of etching the brazing material layer is performed two or more times. If necessary, a chemical polishing step may be combined with the etching of the brazing material layer. By combining the etching of the brazing material layer with chemical polishing, the processing time can be shortened.

[0028] By performing the step of etching the brazing material layer 4 two or more times, it is possible to control the titanium content of the first protruding portion 6 and the second protruding portion 7. In addition, by adjusting the concentration of the etching solution, the treatment time with the etching solution, etc., it is possible to control the length L1 of the first protruding portion 6 and the length L2 of the entire protruding portion. By using the resist, the amount of titanium in the first protruding portion 6, the length L1 of the first protruding portion 6, etc. can be adjusted. The resist is provided at the protruding portion after etching the copper plate, where the second protruding portion is formed. In addition, when the step of etching the brazing material layer 4 is performed multiple times, a method of shortening the etching time of the second and subsequent times compared to the first etching time can be used. A method of etching the side surface of the copper circuit portion 3 after etching the brazing material layer 4 is also effective. The second protruding portion 7 can be formed by etching the side surface of the copper circuit portion 3. If necessary, the second protruding portion 7 may be further etched to provide the first protruding portion 6. By etching the second protruding portion 7, elements other than titanium (e.g., copper) contained in the second protruding portion 7 are removed, and the first protruding portion 6 is formed. A ferric chloride solution can be used as an etching solution for etching the side surface of the copper circuit portion 3. A chemical polishing solution may be used instead of the ferric chloride solution. As the chemical polishing solution, it is preferable to use a chemical polishing solution made by mixing sulfuric acid and hydrogen peroxide. If necessary, an etching mask (resist) is applied to the surface of the copper circuit portion 3.

[0029] It is also possible to combine the etching step of the brazing material layer 4 with the etching step for inclining the side surface of the copper circuit portion 3. As described above, by not allowing the brazing material layer 4 to contain Ag, the brazing material layer 4 becomes more easily etched in the etching step of the copper circuit portion 3. A semiconductor device is obtained by mounting a semiconductor element or the like on the obtained ceramic copper circuit board.

[0030] (Example) (Examples 1 to 6, Comparative Examples 1 to 2) A ceramic substrate 2 shown in Table 1 and a copper plate shown in Table 2 were prepared. All of the copper plates were oxygen-free copper plates.

[0031] [Table 1]

[0032] [Table 2]

[0033] Next, the brazing filler metals shown in Table 3 were prepared.

[0034] [Table 3]

[0035] A brazing filler metal paste was prepared using the brazing filler metal, and a pre-bonding laminate shown in Table 4 was produced. The copper plates were disposed on both sides of the ceramic substrate 2, respectively.

[0036] [Table 4]

[0037] Next, a heat bonding process was performed on the pre-bonding laminate to produce a bonded body. A continuous furnace was used in the heat bonding process. The heating and holding temperature was set to 850°C or higher and 950°C or lower, and the heating and holding time was set to 30 minutes or higher and 60 minutes or lower. The temperature increase rate and temperature decrease rate were set to 20 to 100°C / min. The difference between the temperature increase rate and the temperature decrease rate was set to 20°C / min or lower. The heat bonding process was performed in a nitrogen atmosphere. A bonded body was obtained by the heat bonding process. Bonded bodies 1 to 7 were obtained from pre-bonding laminates 1 to 7, respectively. The resulting bonded bodies were subjected to an etching process to produce ceramic copper circuit boards according to the examples and comparative examples. The configuration of each bonded body is as shown in Table 5. The titanium content, the total amount of titanium and nitrogen, the length L1, the length L2, and the inclination angle θ were measured as described above.

[0038] [Table 5]

[0039] As can be seen from Table 5, the ceramic copper circuit board according to the example had a first protruding portion 6 and a second protruding portion 7. In the second protruding portion 7, Cu was in the range of 5 mass% to 60 mass% and Sn was in the range of 5 mass% to 45 mass%. In contrast, the ceramic copper circuit board according to the comparative example did not have the first protruding portion 6. In the comparative example, only a protruding portion with a titanium content of less than 70 mass% was present. In the ceramic copper circuit board according to the example, the titanium amount in the first protruding portion 6 was 70 mass% or more and the titanium amount in the second protruding portion 7 was less than 70 mass%. Furthermore, the Cu content C1 (mass%) of the joint 5 was compared with the Cu content C2 (mass%) of the second protruding portion 7. The Ti content C3 (mass%) of the joint 5 was compared with the Ti content C4 (mass%) of the second protruding portion 7. The Ti content (mass%) is the total amount (mass%) of titanium and titanium nitride. Furthermore, the shortest distance (pitch) P between adjacent copper circuit portions 3 and the pitch P / copper circuit portion thickness D were measured. The results are shown in Table 6.

[0040] [Table 6]

[0041] A thermal cycle test (TCT test) and a migration test were carried out on the ceramic copper circuit boards according to the examples and comparative examples. The TCT test consisted of one cycle of -50°C x 30 minutes → 25°C x 10 minutes → 155°C x 30 minutes → 25°C x 10 minutes. The silicon nitride substrate was examined for defects after 2000 cycles. The aluminum nitride substrate was examined for defects after 500 cycles. Defects were cracks in the brazing material layer or ceramic substrate. The presence or absence of defects was examined by ultrasonic flaw detection. For each of the examples and comparative examples, tests were conducted on 100 ceramic copper circuit substrates to examine the defect occurrence rate (%). In the migration test, the measurement environment was set to 85°C and humidity to 85%, and a DC voltage of 1000V was applied between the front and back sides of the ceramic copper circuit board on which the pattern was formed, and the board was left for 2000 hours. After leaving the board, the ceramic copper circuit board was dried at 120°C for 2 hours, and then the insulation resistance value between the copper circuit part 3 on the front side and the copper heat sink 8 on the back side, and the insulation resistance value between adjacent copper circuit parts 3 on the front side were measured. A joint with a change rate of 10% or less in insulation resistance value before and after the test was determined as a good product. A joint with a change rate of 11% or more was determined as a defective product. The change rate (%) is calculated by the following formula: [(insulation resistance value after test-insulation resistance value before test) / insulation resistance value before test]×100. The test was performed on 100 ceramic copper circuit boards, and the occurrence rate (%) of defective products was examined. In the migration test, the insulation resistance value between the copper circuit part 3 on the front side and the copper heat sink 8 on the back side was measured for 50 ceramic copper circuit boards, and the insulation resistance value between adjacent copper circuit parts 3 on the front side was measured for another 50 ceramic copper circuit boards. When measuring the insulation resistance value between adjacent copper circuit parts 3 on the front side, wire bonding or copper tape was provided between the copper circuit patterns on the front side as necessary, and these copper circuit patterns were adjusted to have the same potential. The results are shown in Table 7.

[0042] [Table 7]

[0043] As can be seen from Table 7, the ceramic copper circuit board according to the embodiment had good TCT characteristics. Good results were also obtained in the migration test. The TCT characteristics of the ceramic copper circuit boards according to Comparative Example 1 and Comparative Example 2 were equivalent to the TCT characteristics of the ceramic copper circuit board according to the Examples. However, the migration characteristics of the ceramic copper circuit boards according to Comparative Example 1 and Comparative Example 2 were lower than that of the ceramic copper circuit board according to the Examples. For this reason, it is found that providing the first protruding portion and the second protruding portion is effective in further improving the migration characteristics while improving the TCT characteristics.

[0044] Implementations may include the following features. (Feature 1) A ceramic substrate; a copper circuit portion bonded to at least one surface of the ceramic substrate via a brazing material layer; A ceramic copper circuit board comprising: The brazing material layer contains Cu, Ti, and one or two selected from Sn and In, The brazing material layer is a bonding portion provided between the ceramic substrate and the copper circuit portion; a first protruding portion provided around the joint and having a titanium content in the range of 70% by mass or more and 100% by mass or less; Ceramic copper circuit boards. (Feature 2) The brazing material layer further includes a second protruding portion provided between the joint portion and the first protruding portion, 2. The ceramic copper circuit board according to claim 1, wherein the second protruding portion has a titanium content of less than 70 mass %. (Feature 3) The second protruding portion contains 5 mass% or more and 60 mass% or less of Cu and 5 mass% or more and 45 mass% or less of Sn or In, 3. The ceramic copper circuit board according to Feature 2, wherein the total content of titanium and nitrogen in the second protruding portion is within a range of 10 mass % or more and less than 90 mass %. (Feature 4) 4. The ceramic copper circuit board according to any one of Features 2 to 3, wherein a mass ratio of a Cu content in the second protruding portion to a Cu content in the joint portion is 0.7 or less. (Feature 5) 5. The ceramic copper circuit board according to any one of Features 1 to 4, wherein the total content of titanium and nitrogen in the first protruding portion is within a range of 90 mass % or more and 100 mass % or less. (Feature 6) 6. The ceramic copper circuit board according to any one of Features 1 to 5, wherein the total content of titanium and nitrogen in the first protruding portion is within the range of 99 mass % or more and 100 mass % or less. (Feature 7) 7. The ceramic copper circuit board according to any one of Features 1 to 6, wherein, when a length of the first protruding portion in a direction from the joint portion toward the first protruding portion is L1 and a length of a portion of the brazing material layer other than the joint portion in the said direction is L2, 0.3≦L1 / L2≦1 is satisfied. (Feature 8) 8. The ceramic copper circuit board according to any one of Features 1 to 7, wherein the brazing material layer further contains carbon. (Feature 9) 9. The ceramic copper circuit board according to any one of Features 1 to 8, wherein the brazing material layer does not contain Ag. (Feature 10) 10. The ceramic copper circuit board according to any one of Features 1 to 9, wherein the inclination angle of the side surface of the copper circuit portion is within a range of 30 degrees or more and 70 degrees or less. (Feature 11) A plurality of adjacent copper circuit portions are bonded to the at least one surface, 11. The ceramic copper circuit board according to any one of Features 1 to 10, wherein the shortest distance between the multiple copper circuit portions is within a range of 0.2 mm or more and 2 mm or less. (Feature 12) 12. The ceramic copper circuit board according to any one of Features 1 to 11, wherein the ceramic substrate is a silicon nitride substrate. (Feature 13) 13. The ceramic copper circuit board according to any one of Features 1 to 12, wherein the copper circuit portion has a thickness of 0.6 mm or more. (Feature 14) A ceramic copper circuit board according to any one of features 1 to 13, A semiconductor element mounted on the copper circuit portion; A semiconductor device comprising:

[0045] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. [Explanation of symbols]

[0046] 1…Ceramic copper circuit board 2...Ceramic substrate 3...Copper plate 4…Brazing layer 5…Joint part 6…First protruding part 7…Second protruding part 8...Copper heat sink 9...Semiconductor element 10...Semiconductor device L1: Length of the first protruding part L2: Total length of the protruding part P: Shortest distance between adjacent copper plates θ…Angle of inclination of copper circuit side Point A: Contact point between the end of the copper circuit and the brazing layer Point B: Midpoint of the thickness of the copper circuit side Point C: Intersection of the horizontal line from point A and the vertical line from point B

Claims

1. A ceramic substrate; a plurality of copper circuit portions each bonded to at least one surface of the ceramic substrate via a brazing material layer; A ceramic copper circuit board comprising: The brazing material layer does not contain Ag, but contains Cu, Ti, and one or two selected from Sn and In, The brazing material layer is a bonding portion provided between the ceramic substrate and the copper circuit portion; a first protruding portion provided around the joint and having a titanium content in the range of 70 mass% or more and 100 mass% or less; Including, A ceramic copper circuit board, wherein when the thickness of the copper circuit portion is D and the shortest distance between adjacent copper circuit portions is P, the thickness D of the copper circuit portion is 0.1 mm or more and includes a portion where 1≦P / D≦3.

2. The brazing material layer further includes a second protruding portion provided between the joining portion and the first protruding portion, 2. The ceramic copper circuit board according to claim 1, wherein the titanium content in the second protruding portion is less than 70 mass %.

3. The second protruding portion contains 5 mass% or more and 60 mass% or less of Cu and 5 mass% or more and 45 mass% or less of Sn or In, 3. The ceramic copper circuit board according to claim 2, wherein the total content of titanium and nitrogen in the second protruding portion is within a range of 10 mass % or more and less than 90 mass %.

4. 2. The ceramic copper circuit board according to claim 1, wherein the total content of titanium and nitrogen in the first protruding portion is within a range of 90 mass % or more and 100 mass % or less.

5. 2. The ceramic copper circuit board according to claim 1, wherein L1 is a length of the first protruding portion in a direction from the joint toward the first protruding portion, and L2 is a length of the portion of the brazing material layer other than the joint in the said direction, and 0.3≦L1 / L2≦1 is satisfied.

6. 5. The ceramic copper circuit board according to claim 4, wherein L1 is a length of the first protruding portion in a direction from the joint toward the first protruding portion, and L2 is a length of the portion of the brazing material layer other than the joint in the said direction, and 0.3≦L1 / L2≦1 is satisfied.

7. The ceramic copper circuit board according to claim 1 , wherein the brazing material layer further contains carbon.

8. 2. The ceramic copper circuit board according to claim 1, wherein the inclination angle of the side surface of the copper circuit portion is within a range of 30 degrees or more and 70 degrees or less.

9. 7. The ceramic copper circuit board according to claim 6, wherein the inclination angle of the side surface of the copper circuit portion is within a range of 30 degrees or more and 70 degrees or less.

10. 2. The ceramic copper circuit board according to claim 1, wherein the ceramic substrate is a silicon nitride substrate.

11. The ceramic copper circuit board according to claim 9, wherein the ceramic substrate is a silicon nitride substrate.

12. 2. The ceramic copper circuit board according to claim 1, wherein the thickness D of the copper circuit portion is 0.6 mm or more.

13. The ceramic copper circuit board according to claim 10, wherein the thickness D of the copper circuit portion is 0.6 mm or more.

14. The ceramic copper circuit board according to claim 11, wherein the thickness D of the copper circuit portion is 0.6 mm or more.

15. A ceramic copper circuit board according to any one of claims 1 to 14, a semiconductor element mounted on at least one of the plurality of copper circuit portions; A semiconductor device comprising:

Citation Information

Patent Citations

  • Ceramic copper circuit board and method for producing same

    WO2019221174A1

  • Bonded substrate

    WO2020183701A1

  • Joined substrate and production method for joined substrate

    WO2020184510A1

  • Mesh electrode support body for image

    JP1986058144A

  • Ceramic circuit board and its producing method

    JP2003283064A